Dialoguing Across Difference in Adult Second Language Learning - Tara Gibb (Adult Education Research Conference, 2007)
This roundtable discussion attempts “to trouble and worry” an example from teaching practice that raises questions about how difference and identity interrupt dominant discourses during ESL classroom dialogue.